Linguistic Politeness and its Relationship with Data Collection Preferences - Saeedeh Behrooznia; Reza Pishghadam; Mohammad Ghazanfari (Teaching English Language, 2015)
The present study was conducted to investigate the relationship between conceptions of linguistic politeness and data collection preferences. Respectively, the study tried to design and validate a measure of Conception of Linguistic Politeness (CLP) based on Scollon and Scollon’s (1995) model as well as a measure of Data Collection Preferences (DCP). To this end, a total number of 502 individuals completed the CLP scale, and 199 participants filled out the DCP scale. The construct validity of the scales was checked using Confirmatory Factor Analysis (CFA) method. The results of the scales indicated that, the participants of the study tend to use deference politeness system and answer the implicit items more than the explicit ones in research. Furthermore, the relationship between the two scales suggested that the more polite Iranians’ linguistic conceptions get, the more they prefer to answer the implicit items in research. In the end, the results were discussed and the implications were presented.